Second-order nonlinear optical response of metal nanostructures - Locharoenrat, Kitsakorn (My University, 2014)
The second-order responses depend on the structural symmetry of the metal nanostructures, which can give rise to interesting polarization dependences in the responses. We also show that the sensitivity of second-order processes to the symmetry provides important information about plasmonic effects in the nonlinear properties of the structures. © (2014) Trans Tech Publications, Switzerland.
Keywords: Local plasmon; Metal; Nanowires; Second harmonic generation